Intranasal Delivery of Inactivated Influenza Virus and Poly(I:C) Adsorbed Corn-Based Nanoparticle Vaccine Elicited Robust Antigen-Specific Cell-Mediated Immune Responses in Maternal Antibody Positive Nursery Pigs - Patil, Veerupaxagouda; Renu, Sankar; Feliciano-Ruiz, Ninoshkaly; Han, Yi; Ramesh, Anikethana; Schrock, Jennifer; Dhakal, Santosh; HogenEsch, Harm; Renukaradhya, Gourapura J. (Frontiers in Immunology, 2020)
We designed the killed swine influenza A virus (SwIAV) H1N2 antigen (KAg) with Poly(I:C) adsorbed corn-derived Nano-11 particle based nanovaccine called Nano-11-KAg+Poly(I:C), and evaluated its immune correlates in maternally derived antibody (MDA)-positive pigs against a heterologous H1N1 SwIAV infection. Immunologically, in tracheobronchial lymph nodes (TBLN) detected enhanced H1N2-specific cytotoxic T-lymphocytes (CTLs) in Nano-11-KAg+Poly(I:C) vaccinates, and in commercial vaccinates detected CTLs with mainly IL-17A+ and early effector phenotypes specific to both H1N2 and H1N1 SwAIV. In commercial vaccinates, activated H1N2- and H1N1-specific IFNγ+&TNFα+, IL-17A+ and central memory T-helper/Memory cells, and in Nano-11-KAg+Poly(I:C) vaccinates H1N2-specific central memory, IFNγ+ and IFNγ+&TNFα+ and H1N1-specific IL-17A+ T-helper/Memory cells were observed. Systemically, Nano-11-KAg+Poly(I:C) vaccine augmented H1N2-specific IFNγ+ CTLs and H1N1-specific IFNγ+ T-helper/Memory cells, and commercial vaccine boosted H1N2- specific early effector CTLs and H1N1-specific IFNγ+&TNFα+ CTLs, as well as H1N2- and H1N1-specific T-helper/Memory cells with central memory, IFNγ+&TNFα+ and IL-17A+ phenotypes. Remarkably, commercial vaccine induced increase in H1N1-specific T-helper cells in TBLN and naive T-helper cells in both TBLN and PBMCs, while H1N1- and H1N2-specific only T-helper cells were augmented in Nano-11-KAg+Poly(I:C) vaccinates in both TBLN and blood. Furthermore, Nano-11-KAg+Poly(I:C) vaccine stimulated robust cross-reactive IgG and IgA responses in lungs, while the commercial vaccine elicited high levels of serum and lung IgG and serum hemagglutination inhibition titers. In conclusion, despite vast genetic difference (77% in HA gene identity) between the vaccine H1N2 and H1N1 challenge viruses in Nano-11-KAg+Poly(I:C) vaccinates, compared to over 95% identity between H1N1 of commercial vaccine and challenge viruses, the virus load and macroscopic lesions in the lungs of both types of vaccinates were comparable, but the Nano-11-KAg+Poly(I:C) vaccine cleared the virus from the nasal passage better. These data suggested the important role played by Nano-11 and Poly(I:C) in induction of polyfunctional, cross-protective cell-mediated immunity against SwIAV in MDA positive pigs.